CHOLESTEATOMA: A STUDY ON PREOPERATIVE HRCT AND INTRAOPERATIVE CORRELATION - Dr. A. Rajesh Kumar; Dr. S. Sreelatha; Dr. V. Paul Ravi Kumar; Dr. Bandela Mrudula (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background: Chronic otitis media (COM) is a preventable cause of hearing loss characterized by persistent inflammation of the middle ear, which can lead to bone destruction, aural polyps, and complications such as cholesteatoma. Cholesteatoma, a destructive keratinizing cyst, often requires surgical intervention due to the lack of effective medical treatments and the potential for serious intracranial complications. High-Resolution Multi-Detector Computed Tomography (HRMDCT) is now essential in preoperative evaluation of COM, providing detailed imaging of temporal bone anatomy to guide safe and effective surgical planning.Aim of the Study: To compare HRCT findings with intraoperative observations, assess the role of HRCT in patients with cholesteatoma, and determine the extent of cholesteatoma involvement in the temporal bone.Materials: An observational study was conducted at the Government General Hospital, Anantapuramu, between November 2022 and March 2024, including 100 patients with ear-related complaints such as discharge and hearing loss. Patients with chronic squamosal-type CSOM, recurrent ear discharge, with polyps, granulation tissue, or retraction pockets were included. Data analysed in terms of otoscopy signs, radiological imaging (HRCT), and subsequent surgery. Surgeries of Atticotomy, canal wall-down mastoidectomy done. Preoperative HRCT findings were compared with intraoperative results to assess accuracy and correlation.Results: In this study, the majority of patients with cholesteatoma were between 31-40 years old (31%), with females (55%) being more affected than males (45%). Common symptoms included ear pain (79%), ear drainage (67%), and hearing loss (57%). Diabetes and hypertension were present in 18% and 16% of patients, respectively. Otoscopy revealed pars tensa perforation (54%) and PSQ retraction (26%). HRCT findings showed bony wall involvement, with Koerner's septum erosion in 55%, scutum erosion in 39%, and tegmen erosion in 18%. Ossicular involvement included incus erosion in 88%, malleus handle erosion in 35%, and stapes erosion in 11%. Canal involvement included facial canal erosion in 28% and lateral semicircular canal erosion in 6%. HRCT showed excellent correlation with intraoperative findings in most cases, with 100% sensitivity in detecting soft tissue, malleus head erosion, and semicircular canal erosion. Cholesteatoma primarily extended into the antrum, aditus, and epitympanum, with strong statistical correlation between HRCT and intraoperative findings, except for the mesotympanum.Conclusions: This study demonstrates that preoperative HRCT findings show a high correlation with intraoperative findings, supporting its utility in assessing the extent of cholesteatoma. HRCT is particularly valuable in identifying bony erosions, ossicular involvement, and the extent of disease in the middle ear. These insights facilitate optimal surgical planning and potentially improve patient outcomes, highlighting HRCT's importance in the management of cholesteatoma.